Artificial neural networks with bayesian optimization and feature selection applied to regression in engineering problems - Carvalho, Ruan de Alencar (2025)
Dissertação (mestrado) — Universidade de Brasília, Programa de Pós-Graduação em Estruturas e Construção Civil, Faculdade de Tecnologia, 2025.